The effect of a neonatal care educational package on perceived stress in adolescent mothers referring to Zahedan health centers in 2016 - Behjat Tallebi; Zahra Moudi (Tehran University of Medical Sciences, 2019)
Background & Aim: Pregnancy during adolescence is in conflict with the identity structures of adolescents, that can have a negative effect on maternal mental health, and especially cause stress. This study aimed to evaluate the effect of neonatal care education on perceived stress in adolescent mothers. Methods & Materials: This quasi-experimental study was conducted on 116 adolescent pregnant women referred to Zahedan health centers in 2016. Samples were selected by the convenience sampling method and assigned into two groups of 58 people each. The pre-test was performed before the first session using demographic and perceived stress questionnaires. The intervention group received three educational sessions on neonatal care and stress reduction methods. Routine prenatal education was provided to the control group. A post-test was performed at 38 week of pregnancy and 30 days after delivery. The data were analyzed using the Mann-Whitney, Monte Carlo and Fisher tests through the SPSS software version 21. Results: Before the intervention, the stress score for the intervention group was higher than that for the control group (P=0.007), but the mean score of perceived stress for the intervention group significantly decreased at the 38th week of pregnancy and 30 days after delivery, compared to the control group. According to the Mann-Whitney test, the decrease was significant (P˂0.001). Conclusion: Considering the effect of the neonatal care education on reducing stress in adolescent mothers, it is recommended that this type of educational intervention be integrated into care program for adolescent pregnant mothers.